Circulating CCL5 Levels in Patients with Breast Cancer: Is There a Correlation with Lymph Node Metastasis?. (29th May 2013) - Smeets, Ann; Brouwers, Barbara; Hatse, Sigrid; Laenen, Annouschka; Paridaens, Robert; Floris, Giuseppe; Wildiers, Hans; Christiaens, Marie-Rose
Abstract : CC-chemokine ligand 5 (CCL5) was measured in plasma of 238 patients with breast cancer and in serum of 149 of these patients. Mean circulating CCL5 levels tended to be higher in patients with lymph-node-positive breast cancer, larger tumour sizes, the presence of lymphovascular invasion, and multifocal tumours. Additionally, circulating CCL5 levels were higher in the order of stages III, II, and I. The addition of circulating CCL5 concentration to known clinicopathological predictors for lymph node involvement did not allow more precise prediction of the lymph node status. These results suggest that CCL5 is a biomarker for tumour load rather than for lymph node involvement. As such, it might be helpful to identify patients with escape from immunosurveillance who will benefit from therapies to restore immune function.